Spatial Distribution and Association of Gastropods in Mangrove Ecosystem in The Coast of Nusa Lembongan and Perancak Bali - DIANA RIFKA SIMANULLANG; DIETRIECH GEOFFREY BENGEN; NYOMAN M. N. NATIH; NEVIATY PUTRI ZAMANI (Biodiversitas Journal of Biological Diversity, 2024)
Lembongan Island and Perancak are two areas located in Bali Province that have mangrove ecosystems that are utilized as ecotourism areas with different geomorphologies. This study was conducted with the aim to determine the density and spatial distribution of gastropods and their relationship with environmental characteristics using a multivariate analysis approach i.e., Correspondence Analysis (CA) and Principal Component Analysis (PCA). Sampling used a purposive sampling method consisting of 3 zones based on distance from the sea, namely the sea, middle and land zones. The results showed that the most gastropod species in Lembongan Island were found in the sea zone with 17 which the most gastropod species is Pyrene ocellata, while in Perancak the most gastropod species were found in the middle zone with 13 which the most gastropod species is Sphaerasiminea miniata. Environmental characteristics such as temperature, pH, ORP, salinity and dissolved oxygen still support the survival of gastropods. There is twelve mangrove species have found, were Rhizopora stylosa, Rhizopora apiculata, Rhizopora mucronata, Rhizopora lamarckii, Bruguiera gymnorrhiza, Ceriops tagal, Avicennia marina, Avicennia alba, Avicennia rumphiana, Avicennia officinalis, Sonneratia alba, and  Xylocarpus granatum.